Pengaruh Media Sosial dalam Strategi Pemasaran Produk pada UMKM - Nia Paisah Ruminda; Muthia Latifah; Feby Sihaloho (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Social media has become a tool used by everyone. It has become a widely used tool for sharing information and as a promotional platform. In today's digital era, many MSMEs (Micro, Small, and Medium Enterprises) promote their products using social media, eliminating the need to rely entirely on conventional strategies such as direct sales in markets or stores. Marketing utilizes digital technology to achieve goals through active and measurable communication. Marketing strategies using social media are crucial because they can reach a wide range of buyers without time or geographic limitations. Sellers and buyers can interact with each other through messages, comments, and reviews. This research aimed to gain a deeper understanding of how social media influences the marketing strategies implemented by MSMEs through interviews. The results of this study concluded that social media significantly influences MSME marketing strategies and builds relationships with customers. MSMEs are expected to develop better promotional strategies in the future and learn to adapt to competition in the digital era. As a suggestion, MSMEs are advised to integrate interactive content such as live streaming and influencer collaborations to strengthen consumer engagement, as well as allocate a minimum budget of 10-15% of revenue for digital marketing training.